Double trouble? Potential for hyperexcitability following both channelopathic up- and downregulation of Ih in epilepsy - Dyhrfjeld-Johnsen, Jonas; Morgan, Robert J.; Soltesz, Ivan (Frontiers in Neuroscience, 2009)
Studies of pathological ion channel regulation as an underlying mechanism of epilepsy have revealed alterations of the h-current in several animal models. While prior reports indicate that downregulation of the h-current is pro-excitatory on the single neuron level, we recently found an upregulation of Ih in hyperexcitable CA1 pyramidal neuron dendrites following experimental febrile seizures. In addition, in several CA1 pyramidal neuron computational models of different complexity, h-current upregulation has been shown to lead to pro-excitable effects. This focused review examines the complex impact of altered h-current on neuronal resting membrane potential (RMP) and input resistance (Rin), as well as reported interactions with other ionic conductances.